No effect of carbohydrate loading on 1 hr cycle performance - Hawley, J. A.; Palmer, G. S.; Noakes, T. D. (Medicine & Science in Sports & Exercise, 1997)
The effects of supplementing normal diets of trained cyclists (N = 6) with additional carbohydrate (CHO increased by 57%) on muscle glycogen utilization during a 1-hour cycling time trial were investigated. Despite increased muscle glycogen in the CHO-supplement group prior to performance, there was no difference between the conditions in distance cycled during the time trial. Both muscle glycogen utilization and total CHO oxidation were similar under both dietary conditions. It was concluded that CHO supplementation did not produce performance benefits for completing intense, continuous exercise for one hour.